The “Human-animal” Relationship in Psychological Definition Chains - Hajduk, Jan (Respectus Philologicus, 2019)
[full article and abstract in English] The article presents the results of research on definition chains carried out among Polish and German students. Definition chains are systematized hierarchical collections, in which the next lexeme is the superordinate of the previous one, e.g.: Alsatian wolfdog – dog – animal – living creature. The research on definition chains was initiated by R. Martin, French linguist, in the 1970s. Similar analyses were conducted in Poland and Germany 10 years later. The text draws attention to both the inclusive chains, as well as those in which the relation of inclusions does not occur. Non-inclusive definition chains, referred to as psychological chains, indicate the occurrence of the features related to the lexeme of the lowest level, which belong to the linguistic picture of the described word. The relation between “human-animal” and the common top-level domains in both language groups deserve special emphasis.